Lithuanian Schools in the Camps for "Displaced Persons" in Germany in 1945-1950 - Montvilaitė, Sigita (Acta Paedagogica Vilnensia, 1997)
Lithuanian intellectuals managed to create the education system under very difficult and unusual circumstances, having no analogue for their people. In the late forties the organized education of young people made it possible not only to receive a secondary education, but also have to get the opportunity to study at higher schools. The successfulness of the schools was due to the enthusiastic and selfless labour of the teachers. The education boards were working purposefully: the curriculum was organized on time, there were rules of work, guidelines for tuition, social activities of the pupils, and basic syllabuses prepared for all the schools. The heads of the education system managed to make proper contact with the authorities of certain areas of employment and receive get their support and guardianship.
Keywords: history of education; education system; education in exile; education boards; “displaced persons“